A terrifying poison or a cheap fertilizer? The life and death of Mount Vesuvius ash. Issue 2 (June 2021) - Guerra, Corinna
Argument: During the eighteenth century, chemists in the Kingdom of Naples (the South of Italy) were very busy analyzing the chemical composition of ash from Mount Vesuvius. Undoubtedly, after a huge eruption this dusty phenomenon was the most important scientific object of debate. In fact, it was crucial to determine if there were dangerous elements in the ash so that the population could be warned about the potential hazards, such as polluted drinking water. This was not at all a simple issue, as on the other hand there were scholars who realized that ash could be beneficial as a fertilizer, even as clouds of ash had obscured the sun. As chemical inquiries became more precise and the toxic concentration of many elements became known, this double life of Vesuvian ash as a scientific object gradually died.